Spatially and Spectrally Resolved Absorptivity: New Approach for Degradation Studies in Perovskite and Perovskite/Silicon Tandem Solar Cells. Issue 4 (11th December 2019) - Nguyen, Hieu T.; Gerritsen, Sven; Mahmud, Md Arafat; Wu, Yiliang; Cai, Ziyuan; Truong, Thien; Tebyetekerwa, Mike; Duong, The; Peng, Jun; Weber, Klaus; White, Thomas P.; Catchpole, Kylie; et al.
Abstract: Instability in perovskite solar cells is the main challenge for the commercialization of this solar technology. Here, a contactless, nondestructive approach is reported to study degradation across perovskite and perovskite/silicon tandem solar cells. The technique employs spectrally and spatially resolved absorptivity at sub‐bandgap wavelengths of perovskite materials, extracted from their luminescence spectra. Parasitic absorption in other layers, carrier diffusion, and photon smearing phenomena are all demonstrated to have negligible effects on the extracted absorptivity. The absorptivity is demonstrated to reflect real degradation in the perovskite film and is much more robust and sensitive than its luminescence spectral peak position, representing its optical bandgap, and intensity. The technique is applied to study various common factors which induce and accelerate degradation in perovskite solar cells including air and heat exposure and light soaking. Finally, the technique is employed to extract the individual absorptivity component from the perovskite layer in a monolithic perovskite/silicon tandem structure. The results demonstrate the value of this approach for monitoring degradation mechanisms in perovskite and perovskite/silicon tandem cells at early stages of degradation and various fabrication stages. Abstract : Spectrally and spatially resolved absorptivity at sub‐bandgap wavelengths of perovskite materials, extracted from their luminescence spectra, is employed to study degradation across perovskite and perovskite/silicon tandem solar cells. The absorptivity is demonstrated to reflect real degradation in the perovskite film and is much more robust and sensitive than its luminescence spectral peak position, representing its optical bandgap and intensity.